Convective heat transfer due to thermal Marangoni flow about two bubbles on a heated wall - Robinson, Anthony; O'Shaughnessy, Seamus (My University, 2014)
Three dimensional simulations of t hermal Marangoni convection about two bubbles situated on a heated wall immersed in a liquid silicone oil layer have been performed to gain some insight into the thermal and flow interactions between them. The distance between the two bubbles ’ centres was varied between three and twenty five bubble radii to analyse the influence of the inter - bubble spacing on the fl ow and temperature fields and the impact upon local wall heat transfer. For zero gravity conditions, it was determined that the local wall heat flux was greatest for the smallest separation of thre e bubble radii, but that the increase in heat transfer over the whole domain was greatest for a s eparation of ten bubble radii. When the effects of gravity were included in the model, the behaviour was observed to change between the cases. At large separations between the bubbles, increasing the gravity level was found to decrease the local wall heat flux, which was consistent with two - dimensional work. At small separations however, the increase in gravity led to an increase in the local wall heat flux, which was caused by a buoyancy - driven flow formed by the inter action of secondary vortices
PUBLISHED
Keywords: Marangoni; thermocapillary; bubbles; numerical; heat transfer; vortex; enhancement; Smart & Sustainable Planet